2008
DOI: 10.1111/j.1399-5448.2007.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends of type 1 diabetes in Karachi, Pakistan

Abstract: This is the first study in Pakistan to assess the mode of presentation and prevalence of acute and chronic complications in T1DM. Larger scale prospective studies are needed to have more detailed informative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
4
7
0
Order By: Relevance
“…37 The most common causes of diabetic ketoacidosis in children with established type 1 diabetes mellitus are the sudden cessation of subcutaneous insulin or the lack of monitoring. 38 In the present study, 60% of patients presented with disturbed mental status as evidenced by Glasgow Coma Scale scores <15. This can be explained by late referral of patients from peripheral hospitals to our tertiary hospital and supports the notion that a high percentage of children with diabetic ketoacidosis have some element of cerebral injury or dysfunction at the time of presentation even before the initiation of treatment.…”
Section: Discussionsupporting
confidence: 41%
“…37 The most common causes of diabetic ketoacidosis in children with established type 1 diabetes mellitus are the sudden cessation of subcutaneous insulin or the lack of monitoring. 38 In the present study, 60% of patients presented with disturbed mental status as evidenced by Glasgow Coma Scale scores <15. This can be explained by late referral of patients from peripheral hospitals to our tertiary hospital and supports the notion that a high percentage of children with diabetic ketoacidosis have some element of cerebral injury or dysfunction at the time of presentation even before the initiation of treatment.…”
Section: Discussionsupporting
confidence: 41%
“…A study conducted in the province of Sindh, showed higher rate of complication in subjects with T1D. Authors have reported that every fourth person with T1D is suffering from any one of the chronic complication while 2% subjects with T1D had diabetic ketoacidosis (DKA) and 21% had history of DKA[9]. Similar trend was noted in smaller scale studies from this region[8,10].…”
Section: Introductionmentioning
confidence: 57%
“…Polyphagia, polyuria, polydipsia, weight loss history, and DKA history which are confirmed if previous records are present were recorded. In suspected cases of DKA, blood pH, HCO3 was done[9].…”
Section: Methodsmentioning
confidence: 99%
“…Type 1 diabetes mellitus (T1DM) is one of the most common immune-mediated childhood diseases that can lead to early morbidities and mortalities [1]. It can occur at any age, but the peak of its incidence is noted below 18 and over 60 years of age [2][3][4].…”
Section: Introductionmentioning
confidence: 99%